If A = {1, 2, 3, 4}, B = {3, 4, 5, 6}, C = {4, 5, 6, 7, 8} X = (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} then verify the following:
i) A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ B) ∩ (B ∪ C)
ii) A ∩ (B ∪ C) = (A ∩ B) ∪ (A ∩ C)
iii) (A ∪ B)' = A' ∩ B'
iv) (A ∩ B)' = A' ∪ B'
v) A = (A ∩ B) ∪ (A ∩ B')
vi) B = (A ∪ B) ∪ (A' ∩ B)
vii) n (A ∪ B) = n(A) + n(B) - n(A ∩ B)
Answers
Answer:
Step-by-step explanation:
Hi,
Given A = {1, 2, 3, 4}, B = {3, 4, 5, 6}, C = {4, 5, 6, 7, 8}
X = (1, 2, 3, 4, 5, 6, 7, 8, 9, 10}
i)A ∪ (B ∩ C) = (A ∪ B) ∩ (A ∪ C)
Consider L.H.S = A ∪ (B ∩ C)
= {1, 2, 3, 4} ∪ {{3, 4, 5, 6} ∩ {4, 5, 6, 7, 8}}
= {1, 2, 3, 4} ∪ {4, 5, 6}
= {1, 2, 3, 4, 5, 6}
Consider R.H.S = (A ∪ B) ∩ (A ∪ C)
(A ∪ B) = {1, 2, 3, 4} ∪ {3, 4, 5, 6} = {1, 2, 3, 4, 5, 6}
(A ∪ C) = {1, 2, 3, 4} ∪ {4, 5, 6, 7, 8} = {1, 2, 3,4, 5, 6, 7, 8}
(A ∪ B) ∩ (A ∪ C) = {1, 2, 3, 4, 5, 6}
Thus, L.H.S = R.H.S
ii)A ∩ (B ∪ C) = (A ∩ B) ∪ (A ∩ C)
Consider L.H.S = A ∩ (B ∪ C)
= {1, 2, 3, 4} ∩ {{3, 4, 5, 6} ∪ {4, 5, 6, 7, 8}}
= {1, 2, 3, 4} ∩ {3, 4, 5, 6, 7, 8}
= {3, 4}
Consider R.H.S = (A ∩ B) ∪ (A ∩ C)
(A ∩ B) = {1, 2, 3, 4} ∩ {3, 4, 5, 6} = {3, 4}
(A ∩ C) = {1, 2, 3, 4} ∩ {4, 5, 6, 7, 8} = {4}
(A ∩ B) ∪ (A ∩ C) = { 3, 4}
Thus, L.H.S = R.H.S
(iii)(A ∪ B)' = A' ∩ B'
Consider L.H.S = (A ∪ B)'
= X - (A ∪ B)
(A ∪ B) = {1, 2, 3, 4} ∪ {3, 4, 5, 6} = {1, 2, 3, 4, 5, 6}
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} - {1, 2, 3, 4, 5, 6}
= {7, 8, 9, 10}
Consider R.H.S = A' ∩ B'
A' = X - A
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} - {1, 2, 3, 4)
= {5, 6, 7, 8, 9, 10}
B' = X - B
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} -{3, 4, 5, 6}
= {1, 2, 7, 8, 9, 10}
A' ∩ B' = {5, 6, 7, 8, 9, 10} ∩ {1, 2, 7, 8, 9, 10}
= { 7, 8, 9, 10}
Thus, L.H.S = R.H.S.
iv)(A ∩ B)' = A' ∪ B'
Consider L.H.S = (A ∩ B)'
= X - (A ∩ B)
(A ∩ B) = {1, 2, 3, 4} ∩ {3, 4, 5, 6} = {3, 4}
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} - {3, 4}
= (1, 2, 5, 6, 7, 8, 9, 10}
Consider R.H.S = A' ∪ B'
A' = X - A
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} - {1, 2, 3, 4)
= {5, 6, 7, 8, 9, 10}
B' = X - B
= (1, 2, 3, 4, 5, 6, 7, 8, 9, 10} -{3, 4, 5, 6}
= {1, 2, 7, 8, 9, 10}
A' ∪ B' = {5, 6, 7, 8, 9, 10} ∪ {1, 2, 7, 8, 9, 10}
= { 1, 2, 5, 6, 7, 8, 9, 10}
Thus, L.H.S = R.H.S.
v) A = (A ∩ B) ∪ (A ∩ B')
Consider R.H.S = (A ∩ B) ∪ (A ∩ B')
(A ∩ B) = {1, 2, 3, 4} ∩ {3, 4, 5, 6} = {3, 4}
(A ∩ B') = {1, 2, 3, 4} ∩ {1, 2, 7, 8, 9, 10}
= { 1, 2}
(A ∩ B) ∪ (A ∩ B') = {3, 4} ∪ {1, 2}
= {1, 2, 3, 4}
= A
Thus, L.H.S = R.H.S
vi) B = (A ∪ B) ∪ (A' ∩ B)
Consider R.H.S = (A ∩ B) ∪ (A' ∩ B),
(A ∩ B) = {1, 2, 3, 4} ∪ {3, 4, 5, 6} = {3, 4}
(A' ∩ B) = {5, 6, 7, 8, 9, 10} ∩ {3, 4, 5, 6} = {5, 6}
(A ∩ B) ∪ (A' ∩ B) = {3, 4} ∪ {5, 6}
= {3, 4, 5, 6}
= B
vii) n (A ∪ B) = n(A) + n(B) - n(A ∩ B)
Consider L.H.S = n (A ∪ B)
(A ∪ B) = {1, 2, 3, 4} ∪ {3, 4, 5, 6} = {1, 2, 3, 4, 5, 6}
n(A ∪ B) = 6
Consider R.H.S = n(A) + n(B) - n(A ∩ B)
n(A) = 4
n(B) = 4
(A ∩ B) = {1, 2, 3, 4} ∪ {3, 4, 5, 6} = {3, 4}
n(A ∩ B) = 2
So, n(A) + n(B) - n(A ∩ B)
= 4 + 4 - 2
= 6
Thus, L.H.S = R.H.S
Hope, it helps !